2017
DOI: 10.5005/jp-journals-10024-2062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sandblasting Angle and Distance on Biaxial Flexural Strength of Zirconia-based Ceramics

Abstract: Aim: Surface treatment is necessarily required for bonding of zirconia to the veneering porcelain and luting cements. Sandblasting is the most common and probably the most efficient surface treatment method. Sandblasting roughens the surface and may affect the flexural strength of zirconia. Different sandblasting protocols may yield variable results. This study sought to assess the effect of sandblasting angle and distance on the biaxial flexural strength of zirconia-based ceramics. Materials and methods:This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In addition, the sandblasting can be effective to increase the surface area, surface wettability, and therefore the surface energy [11]. However, the bonding performance would be highly dependent on the sandblasting conditions, such as the size and shape of abrasive particles [12,13], air pressure [12,14], working duration [15], distance [14,16], and impact angle [16]. The sandblasting tends to trigger the tetragonal to monoclinic phase transformation of conventional high-strength zirconia (3Y-TZP) [17], whereby the transformation toughening mechanism [2] can lead to increased mechanical strengths [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the sandblasting can be effective to increase the surface area, surface wettability, and therefore the surface energy [11]. However, the bonding performance would be highly dependent on the sandblasting conditions, such as the size and shape of abrasive particles [12,13], air pressure [12,14], working duration [15], distance [14,16], and impact angle [16]. The sandblasting tends to trigger the tetragonal to monoclinic phase transformation of conventional high-strength zirconia (3Y-TZP) [17], whereby the transformation toughening mechanism [2] can lead to increased mechanical strengths [14].…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate sandblasting protocols on the durable bond between resin cement and highly translucent zirconia have not well been studied yet. Moreover, most of the previous studies on the various effects of alumina sandblasting have used only a few particle sizes; 50 µm [14,18,[33][34][35][36], 50 and 110 µm [9,12,15], 110 µm [16], 150 µm [13], 110 and 250 µm [17]. This study focused on the influence of the sandblasting particles with five different sizes on the sandblasting performance of dental monolithic zirconia with three different levels of translucency, while other sandblasting parameters were kept constant.…”
Section: Introductionmentioning
confidence: 99%
“…In this experiment, both chemical treatment with MDP and mechanical treatment via alumina sandblasting were used. Mechanical treatment via sandblasting is affected by various parameters, such as particle size 27) , air pressure 27) , sample-nozzle distance 28) , working time 19) , and impact angle 28) , and the optimal protocol for treatment of translucent zirconia is still unclear. Previous studies have reported different optimal particle sizes and pressures for achieving reliable bond strength, with some suggesting that 50 µm and 0.2 MPa are the most effective 29,30) , whereas others have found that larger particles or higher pressures can increase bond strength 31,32) .…”
Section: Discussionmentioning
confidence: 99%
“…Grit-blasting at a close distance is found to initiate heat, chipping, and cracking of the zirconia surface, thereby generating residual stresses through which strength reducing flaws are introduced [27]. On the contrary, increased distance is associated with lower surface roughness resulting in decreased or unacceptable zirconia adhesion strength [26,27].…”
Section: Discussionmentioning
confidence: 99%